Ultrastructural evidences of the occurrence of digestion and absorption of organic solutes in bees ileum (Melipona quadrifasciata anthidioides - Hymenoptera, Apidae) - CruzLandim, C. (Nuova Immagine Editrice, 1996)
The ultrastructural aspects of the ileum of Melipona quadrifasciata anthidioides, a stingless bee whose workers obtain their protein requirements from pollen, present morphological evidences of digestion and absorption. These evidences are represented by special relationships between food particles and the bacterial nora present and between their assemblage and the ileum wall, mainly in the ileum three anterior fourths. The apical features of the epithelium also are indicative of organic material absorption.
Keywords: ileum; stingless bee; digestion; absorption; bacteria; morphology